Characteristics of the complete chloroplast genome of Halophila beccarii. Issue 1 (2nd January 2020) - Yu, Shuo; Li, Xiaojuan; Jiang, Kai; Chen, Xuyang; Wang, Xiangping
Abstract: Halophila beccarii has been listed as a vulnerable species in ICNU. In this study, the complete plastid genome sequence of H. beccarii was successfully sequenced by the technology of Illumina. The whole plastid genome length was 168, 585 bp and contained a typical quadripartite structure including one large single-copy (LSC) region (80, 881 bp), one small single-copy (SSC) region (4, 730bp) and a pair of inverted repeats (IR) regions (41, 487bp). The GC content of this genome was 38.5%. The whole genome contained 132 genes including 88 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. The phylogenetic analysis indicated that H. beccarii and Thalassia hemprichii formed a distinct clade.